TINJAUAN PENGGUNAAN ABU SISA PEMBAKARAN BATU BARA PABRIK DILEM TERHADAP KUAT TEKAN BETON - Dwi Sri Wiyanti; Taufik Dwi Laksono; Atiyah Barkah (KURVATEK, 2020)
Many concrete study studied the use of substitute material that is fly ash, a coal combustion product from the steampowered electric generator. Coal is also used by PT. SCI, a Dilem leaves processing industry in Purbalingga regency. To determine whether the utilization of the residual ash from coal combustion of Dilem leaves industry meet the required compressive strength, a study was conducted on the compressive strength of concrete that use coal combustion ashes from PT SCI. The purpose of this study is to find out the effect of using coal combustion ash on concrete compressive strength and to find out the deviation in compressive strength of concrete that produced with the 10%, 12.5%, 15%, and 17.5% of coal combustion ashes on the weight of cement. The use of coal combustion ash affects the compressive strength of concrete and 12.5% of coal combustion ash as a cement substitution gives the maximum compressive strength that is 23.0 Mpa.Keywords: Concrete, Compressive Strength of Concrete, Fly Ash, Coal Combustion Ash